2016
DOI: 10.3122/jabfm.2016.04.150315
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Level as Diagnostic Marker in Young Febrile Children Presenting in a General Practice Out-of-Hours Service

Abstract: Background: It is unclear how well a C-reactive protein (CRP) value predicts a serious infection (SI) in young febrile children in general practice.Methods: This prospective cohort study with 1-week follow-up included children, aged 3 months to 6 years, presenting with fever to a general practitioner out-of-hours service. We evaluate whether CRP level has predictive value for diagnosing a child at risk for an SI either at presentation or during followup. The index test was CRP <20 mg/L (rule out an SI) and >80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…CRP levels in this study correspond with reported levels in adults 32 and children with respiratory infections. 27,36 Most children had low CRP levels, as is expected in a primary care setting, because most children suffer from non-serious illnesses. In a recent Norwegian study in children with fever and/or respiratory symptoms presenting to out-of-hours services, antibiotics were prescribed to 13% of children with CRP levels <20 mg/L.…”
Section: Discussionmentioning
confidence: 92%
“…CRP levels in this study correspond with reported levels in adults 32 and children with respiratory infections. 27,36 Most children had low CRP levels, as is expected in a primary care setting, because most children suffer from non-serious illnesses. In a recent Norwegian study in children with fever and/or respiratory symptoms presenting to out-of-hours services, antibiotics were prescribed to 13% of children with CRP levels <20 mg/L.…”
Section: Discussionmentioning
confidence: 92%
“…CRP is not recommended as routine blood testing in general practice, and its rise in this setting likely represents inappropriate use. 23 In the case of vitamin D testing, NICE guidance only recommends testing in children if they have musculoskeletal symptoms, abnormal serum bone profile or X-Ray findings, suspected bone disease such as osteomalacia or known bone disease such as osteoporosis. 24 A retrospective analysis of vitamin D testing across all age-groups in the Northumbria Healthcare NHS Trust from 2002 to 2017 found a similar rise in testing rates.…”
Section: Discussionmentioning
confidence: 99%
“…12 C reactive protein levels in typhoid C-reactive protein (CRP) is an acute-phase protein with increased concentrations in the blood during infections. 13 CRP belongs to the pentraxin family of proteins, because it has five identical subunits, encoded by a single gene on chromosome 1, which associate to form a stable disc-like pentameric structure. 14 Bacterial or inflammatory diseases raise the level of CRP.…”
Section: Lipid Profilementioning
confidence: 99%